Preferentially Expressed Antigen in Melanoma (PRAME) and the PRAME Family of Leucine-Rich Repeat Proteins - Hermes, Nora; Kewitz, Stefanie; S. Staege, Martin (Current Cancer Drug Targets, 2016)
Preferentially expressed antigen in melanoma (PRAME) is the best characterized member of the PRAME family of leucine-rich repeat (LRR) proteins. Mammalian genomes contain multiple members of the PRAME family whereas in other vertebrate genomes only one PRAME-like LRR protein was identified. PRAME is a cancer/testis antigen that is expressed at very low levels in normal adult tissues except testis but at high levels in a variety of cancer cells. In contrast to most other cancer/testis antigens, PRAME is expressed not only in solid tumors but also in leukemia cells. Expression of PRAME and other members of the PRAME family is regulated epigenetically. PRAME interacts with varying pathways that might be directly involved in the malignant phenotype of cancer cells. For instance, PRAME is able to dominantly repress retinoic acid signaling in these cells. On the other hand, PRAME-derived peptides can be recognized as epitopes by cytotoxic T cells and PRAME represents an attractive target for immunological treatment strategies.
Keywords: DNA methylation